Synthesis of phenazines from ortho-bromo azo compounds via sequential Buchwald-Hartwig amination under micellar conditions and acid promoted cyclization. Issue 46 (12th November 2020) - Yousif, Dawod; Monti, Mauro; Papagni, Antonio; Vaghi, Luca
Graphical abstract: Highlights: Phenazines are obtained via tandem amination\cyclization of ortho -bromo azobenzenes. The micellar B-H step is achieved in water without the need of inert atmosphere. Ortho -bromo azobenzenes are prepared by selective bromination or diazo coupling. Abstract: Non-symmetric phenazines were synthesized via the Buchwald-Hartwig amination of ortho -bromoazobenzenes with anilines under micellar conditions, using the commercially available surfactant Kolliphor EL in water, followed by an acid-promoted 6π-electrocyclization-aromatization process. Two different synthetic pathways to obtain the ortho -bromo azo intermediates were explored, namely the palladium catalysed selective ortho bromination of azobenzenes and the diazo coupling of ortho -bromo diazonium salts with N, N -dimethylaniline, imidazole, phenol, sodium methanesulfinate and ethyl chloroformate.